IJTIMOIY-PSIXOLOGIK TADQIQOTLARDA AVLODLAR TASNIFI - Abibullaeva, P. (SCIENCE and SOCIETY, 2025)
This article describes the theory of generations, according to the classification of four generations, the “BB” (Baby Boomers) generation, “X” generation, “Y” generation (millennials), “Z” generation (Zumers) personality traits, and the content of priority values of these generations.